2016
DOI: 10.1017/s0007114515005309
|View full text |Cite
|
Sign up to set email alerts
|

A healthy Nordic diet and physical performance in old age: findings from the longitudinal Helsinki Birth Cohort Study

Abstract: Epidemiological studies have shown that a number of nutrients are associated with better physical performance. However, little is still known about the role of the whole diet, particularly a healthy Nordic diet, in relation to physical performance. Therefore, we examined whether a healthy Nordic diet was associated with measures of physical performance 10 years later. We studied 1072 participants from the Helsinki Birth Cohort Study. Participants' diet was assessed using a validated 128-item FFQ at the mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 45 publications
1
62
0
Order By: Relevance
“…HBCS has been described in detail previously (5,11). The present sub-study includes 1078 participants (603 women and 475 men) born between 1934 and 1944.…”
Section: Methodsmentioning
confidence: 99%
“…HBCS has been described in detail previously (5,11). The present sub-study includes 1078 participants (603 women and 475 men) born between 1934 and 1944.…”
Section: Methodsmentioning
confidence: 99%
“…The dotted vertical lines correspond to the 10th, 25th, 50th, 75th and 90th percentile of the healthy Nordic diet score These different versions of a healthy Nordic diet have had beneficial associations with several disease risk factors, such as hypertension [8], abdominal obesity and weight gain [5,10,25], inflammation [7] and serum lipids [9], although one study reported an association with decreased HDL cholesterol [26]. Higher adherence to a healthy Nordic diet has also been associated with lower risk of colorectal cancer in women [12], better cognition [27], greater muscle strength and physical capacity in old age [6,28], and with reduced risk of myocardial infarction [15,16], stroke [17], total mortality [11,13,14] and type 2 diabetes [19], although some studies have observed no association with risk of type 2 diabetes [18] or cardiovascular disease [29]. Overall, however, a higher adherence to a healthy Nordic diet appears to be associated with beneficial health outcomes, and our current findings add to the knowledge of the potential health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…A high Baltic Sea Diet Score is characterized by high consumption of berries and fruits, whole grains, vegetables, rapeseed oil, fish, low-fat dairy and low consumption of processed meat and alcohol [4]. Earlier studies have shown that a higher Baltic Sea Diet Score is associated with, for example, lower risk of abdominal obesity [5], better physical capacity in old age [6] and lower risk of elevated C-reactive protein concentration [7]. Other similar diet scores that have been developed to define a healthy Nordic diet have also observed beneficial associations with disease risk factors [8][9][10], although less is known of the associations with risk of diseases or mortality and the findings are inconclusive [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, compared with the Mediterranean diet, other regional diet interventions have been investigated less and should be considered seriously. For instance, it has been proven that the Nordic diet increased physical performance and may be adopted to prevent type-2 diabetes [ 60 , 61 ]. Therefore, additional studies are needed to investigate the effect of other types of diet to change older people’s eating behaviour.…”
Section: Discussionmentioning
confidence: 99%